Andrographolide Promotes Neural Differentiation of Rat Adipose Tissue-Derived Stromal Cells through Wnt/β-Catenin Signaling Pathway. (20th September 2017) - Liang, Yan; Li, Miao; Lu, Tao; Peng, Wang; Wu, Jian-Huang
Abstract : Adipose tissue-derived stromal cells (ADSCs) are a high-yield source of pluripotent stem cells for use in cell-based therapies. We explored the effect of andrographolide (ANDRO, one of the ingredients of the medicinal herb extract) on the neural differentiation of rat ADSCs and associated molecular mechanisms. We observed that rat ADSCs were small and spindle-shaped and expressed multiple stem cell markers including nestin. They were multipotent as evidenced by adipogenic, osteogenic, chondrogenic, and neural differentiation under appropriate conditions. The proportion of cells exhibiting neural-like morphology was higher, and neurites developed faster in the ANDRO group than in the control group in the same neural differentiation medium. Expression levels of the neural lineage markers MAP2, tau, GFAP, and β -tubulin III were higher in the ANDRO group. ANDRO induced a concentration-dependent increase in Wnt/ β -catenin signaling as evidenced by the enhanced expression of nuclear β -catenin and the inhibited form of GSK-3 β (pSer9). Thus, this study shows for the first time how by enhancing the neural differentiation of ADSCs we expect that ANDRO pretreatment may increase the efficacy of adult stem cell transplantation in nervous system diseases, but more exploration is needed.